Penerapan Metode Kooperatif Tipe Learning Together Untuk Meningkatkan Hasil Belajar Seni Budaya di SMAN 8 Denpasar - Gusti Ayu Made Puspawati; Gusti Ayu Agung Trisna Prameswari; Mirah Rahmawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
After conducting initial observations at SMK Negeri 8 Denpasar, it was discovered that the students' learning outcomes in cultural arts subjects were relatively low. Therefore, the researcher decided to conduct further study using the PTK (Classroom Action Research) approach method. The aim of implementing the PTK method was to enhance students' understanding of the cultural arts subject through a cooperative learning model known as